Writing (Recording of) Teaching Practices as a Way to Generate Knowledge in Undergraduate Majors - García Vargas, Silvia E. (2020)
This article is part of an international research project called “Writing about teaching practices in undergraduate programs in Brazil, Costa Rica, and Honduras: record, analysis, and production of knowledge”, whose goal has been to discuss the role of writing in undergraduate courses at participating universities. Our analysis is about the discussion of the role of reading and writing in addition to presenting texts produced by professors from Universidade do Estado de Mato Grosso, Brazil and Universidad Nacional, Costa Rica in order to analyze the impact that writing time has for training and how this task should be seen by professors as a way to transform learning from the union of theory, practice, and the reflection carried out by the students.